Arab Nation-building through Detective Stories in al-Ḍiyāʾ: The Cultural Translations of Nasīb al-Mashʿalānī - Zachs, Fruma (Die Welt des Islams, 2020)
This article examines detective stories translated by Nasīb al-Mashʿalānī published in the periodical al-Ḍiyāʾ ("The Gleam") and their contribution to the process of Arab nation-building at the turn of the twentieth century. We show how al-Mashʿalānī's work consisted of a cultural process rather than a textual product or linguistic transfer. These translations introduced new social, political and epistemological concepts that were particularly important to societal changes in the Arab world - such as the notion of civil society, the relationship of the public to institutions of law and the police, the pursuit of justice, and ways of dealing with crime in the Western model of law and order - that al-Mashʿalānī deliberately adapted to the local Arab culture.